2010
DOI: 10.1177/0363546510376816
|View full text |Cite
|
Sign up to set email alerts
|

Overuse Injuries in Professional Road Cyclists

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Clarsen, B., Krosshaug, T., Bahr, R. (2010). Overuse injuries in professional road cyclists. American Journal of Sports Medicine, 38, 2494Medicine, 38, -2501 Dette er siste tekst-versjon av artikkelen, og den kan inneholde ubetydelige forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på ajs.sagepub.com: http://dx.doi.org/10.1177/0363546510376816This is the final text version of the article, and it may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
139
3
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 30 publications
10
139
3
19
Order By: Relevance
“…Indoor cycling has also become a popular activity, and studies of competitive cyclists show that overuse injuries are common, particularly in the knee and low back. (Clarsen, Krosshaug, & Bahr, 2010) Even yoga may lead to acute injuries such as rupture of the lateral collateral ligament, and musculoskeletal pain in especially the low back (Holton & Barry, 2014;Patel & Parker, 2008) Knowledge regarding injuries and injury prevention among group fitness instructors is limited. One study found the risk of injuries among instructors in aerobic dance to be twice as high as among the participants in these classes.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor cycling has also become a popular activity, and studies of competitive cyclists show that overuse injuries are common, particularly in the knee and low back. (Clarsen, Krosshaug, & Bahr, 2010) Even yoga may lead to acute injuries such as rupture of the lateral collateral ligament, and musculoskeletal pain in especially the low back (Holton & Barry, 2014;Patel & Parker, 2008) Knowledge regarding injuries and injury prevention among group fitness instructors is limited. One study found the risk of injuries among instructors in aerobic dance to be twice as high as among the participants in these classes.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo estudos epidemiológicos, a lombalgia acomete de 30 a 60% dos ciclistas (WILBER et al, 1995;CALLAGHAN;JARVIS, 1996;CLARSEN;KROSSHAUG;BAHR, 2010), representando uma das queixas mais comuns entre as disfunções musculoesqueléticas neste esporte (WILBER et al, 1995;CALLA-GHAN;JARVIS, 1996;VILLAVICENCIO et al, 2006;LITTLE;MANSOOR, 2008;CLARSEN, KROSSHAUG;BAHR, 2010). O gênero e a massa corporal são fatores que não apresentam influência sobre a ocorrência de lombalgia em ciclistas, diferente do que ocorre com o fator idade.…”
Section: Discussionunclassified
“…Mais de 49 milhões de norte americanos utilizam a bicicleta mensalmente, dos quais mais de 5 milhões pedalam pelo menos vinte dias no mês (ASPLUND; ROSS, 2010). No entanto, a prática do ciclismo, ou mesmo o uso da bicicleta como meio de transporte, muitas vezes é prejudicada por lesões por esforço repetitivo, levando à diminuição da frequência de uso da bicicleta (CLARSEN;KROSSHAUG;BAHR, 2010). Dentre estas disfunções, a dor lombar (lombalgia) é uma das mais frequentes, podendo perdurar após o término da prática ciclística, apresentando ocorrência unilateral (SANNER; O'HALLORAN, 2000) ou bilateral (SANNER; O' HALLORAN, 2000;LITTLE;MANSOOR, 2008).…”
Section: Introductionunclassified
“…Eine umfangreiche Studie von Clarsen et al [17] wies als Hauptsymptome LWS-Beschwerden ("lower back pain") mit 58 % und den vorderen Knieschmerz ("anterior knee pain") mit 36 % nach. Weiterhin konnte gezeigt werden, dass weniger die LWS-als vielmehr die Kniebeschwerden ursächlich für einen Trainingsausfall waren.…”
Section: Introductionunclassified